The role of financial regulator in protecting bank consumers from unfair contract terms: the case of Malaysian Islamic banks - Abu Bakar, Noor Mahinar; Mohd Yasin, Norhashimah; Razali, Siti Salwani; Ng, See Teong (Emerald Publishing Limited, 2019)
This chapter aims to examine Bank Negara Malaysia’s (BNM) approach in fulfilling its financial consumer protection mandate from unfair contract terms and the statutory framework relevant for consumer protection in the domestic market. This is a qualitative-based research. Using content analysis, this study analyses BNM’s Financial Stability and Payment Systems Report from 2012 to 2016, specifically on the ‘market conduct and consumer empowerment’ to explore BNM’s prudential regulatory, supervisory and consumer protection roles in protecting bank consumers from unfair contract terms. It is found that even if a number of standards and guidelines have been issued by BNM in improving ‘fairness and transparency’, the potential risk facing bank consumers from unfair terms in standard consumer contracts of Islamic banks especially where terms may be unfair or unclear remains unchanged. This study recommends that BNM as the Central Bank and financial regulator of Malaysia promotes self-regulation of the Islamic banks by adopting value-based banking of a consumer-focussed culture in delivering an effective protection for consumers from unfair contract terms and empowering them in their dealings with Islamic banks in Malaysia. This study will be helpful in bringing a policy formulation by BNM in identifying their weak areas and suggesting improvements in pursuing a strong consumer protection agenda from unfair contract terms.